Facial Paralysis From Post-transplant Lymphoproliferative Disorder. Issue 5 (June 2021) - Toivonen, Joonas; Shulman, David S.; Shusterman, Suzanne; Robson, Caroline D.; Saillant, Meredith; Poe, Dennis
Abstract : Objective: We report a case of facial paresis and profound hearing loss from post-transplant lymphoproliferative disorder (PTLD) in a pediatric patient with neuroblastoma. Patient: Three-year-old boy with rapidly progressive right facial paresis and sensorineural hearing loss. High-risk neuroblastoma had been diagnosed 1 year earlier, treated with chemotherapy and resection of the adrenal primary tumor. Two months after two autologous hematopoietic stem cell transplantations (HSCT), the patient developed facial paralysis. Magnetic resonance imaging (MRI) showed bilateral progressive internal auditory canal (IAC) enhancing lesions with a mass lesion on the right and wispy enhancement on the left and enhancement within the right cochlea. Lumbar puncture (LP) was positive for Epstein-Barr virus (EBV) making the diagnosis of PTLD most probable. Biopsy of the right IAC lesion was deferred because of potential procedural risks including intradural spread of tumor or fungus. The patient was treated with anti-fungal therapy and systemic rituximab without improvement. Subsequent intrathecal rituximab resulted in improvement of lesions on MRI and clearance of EBV from the cerebrospinal fluid (CSF). Interventions: Mastoidectomy for biopsies from the mastoid and middle ear. Intrathecal treatment with rituximab. Main Outcome Measures: Imaging assessment of IAC lesion, CSF EBV titers, facial nerve function. Results: Gradual resolution of IAC mass lesions, remission of PTLD, and facial improvement from House–Brackmann score of 4 to 3. Conclusions: PTLD causing facial paresis after autologous HSCT has not been previously reported and may be considered in the differential diagnosis of lesions causing facial paresis in patients who have received a stem cell or solid organ transplant.